Overview of the CMS beam loss monitoring system (BCML) and diamond detectors surface modification; Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment; Vol. ХХХ (In Press, Corrected Proof) - Okhotnikov V. V. Vitaly Vladimirovich (2018, 2018)
Title screen